Sosialiasasi Pemilih Pemula 2020 pada Pilkada di Tengah Pandemi Covid-19 di SMA dan SMK Wisnuwardhana Malang - wahyu Hindiawati; Rika Novitasari; Tikka Dessy Harsanti; Erifano Dimas Ramadhan; Pipit Izatul Masruroh (Idea Pengabdian Masyarakat, 2022)
General election or what is often abbreviated as Election is the process of selecting people to fill certain political positions. These positions are varied, ranging from president, people's representatives at various levels of government, to village heads. At the local level, the means of implementing democracy are called regional head elections or pilkada. Beginner Voters are the basis of voters who use their rights for the first time in the 2020 simultaneous elections. In this community service, the aim is to provide socialization to Wisnuwardhana Malang High School students about the 2020 Beginner Voters "Pilkada in the Middle of the Covid-19 Pandemic". The method used in this study is an empirical legal research method, namely by looking for data obtained directly from the community as the first source through field research, which is carried out either through observation (observation), interviews, or distributing questionnaires in SMA-SMK Wisnuwardhana Malang. The participants of this socialization were 26 students. The result of this community service is that there is a socialization of local election novice voters in the midst of the Covid-19 pandemic which was carried out at the Wisnuwardhana High Schools. . While the level of achievement in this program is 90%.